2011
DOI: 10.1073/pnas.1104521108
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of nuclear pore transport yield mechanistic insights and quantitative predictions

Abstract: To study transport through the nuclear pore complex, we developed a computational simulation that is based on known structural elements rather than a particular transport model. Results agree with a variety of experimental data including size cutoff for cargo transport with (30-nm diameter) and without (<10 nm) nuclear localization signals (NLS), macroscopic transport rates (hundreds per second), and single cargo transit times (milliseconds). The recently observed bimodal cargo distribution is predicted, as is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 27 publications
3
72
0
Order By: Relevance
“…Even so, our model of the FG-Nups is coarsegrained in the sense that it makes no distinction between the hydrophobicities of the different amino acids, does not explicitly incorporate hydrogen bonding, and does not include specific interchain binding [e.g., as observed in the formation of gels with Asn-rich FG sequences (35)]. We have also omitted specific binding interactions between the model particles and the FG domains in the FG-Nups; these interactions have been proposed to play a role in the kap-mediated translocation mechanism (11,21,23,36,37). The association between the kaps and the FG domains is weak (36,38) and dynamical (22); therefore, the nature of this interaction is probably between high-affinity ligandreceptor binding and the hydrophobic interaction modeled here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even so, our model of the FG-Nups is coarsegrained in the sense that it makes no distinction between the hydrophobicities of the different amino acids, does not explicitly incorporate hydrogen bonding, and does not include specific interchain binding [e.g., as observed in the formation of gels with Asn-rich FG sequences (35)]. We have also omitted specific binding interactions between the model particles and the FG domains in the FG-Nups; these interactions have been proposed to play a role in the kap-mediated translocation mechanism (11,21,23,36,37). The association between the kaps and the FG domains is weak (36,38) and dynamical (22); therefore, the nature of this interaction is probably between high-affinity ligandreceptor binding and the hydrophobic interaction modeled here.…”
Section: Discussionmentioning
confidence: 99%
“…The kap-cargo complex particle interacts with the FG residues in this layer as it diffuses through the channel. Another simulation study suggested that the translocating particle remains bound to the same Nup for its entire trajectory through the NPC (21). The differences between these works arise due to the choice of the molecular model, which, in neither case, considered the specific sequence and length of the FG-Nups and the particular properties of each amino acid in the sequence (e.g., hydrophobicity, charge).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another large protein-membrane assembly at the sub-cellular scale is the nuclear pore complex (NPC) [94, 95], located in the double bilayers of the nuclear envelope mediating particle exchange between nucleus and cytoplasm. Nsp1, a nuclear pore protein, is the major component of NPC.…”
Section: Diverse Applicability Of Large-scale Simulationsmentioning
confidence: 99%
“…Another model, the Di-block Copolymer Brush Gate (DCBG) model [11], Fig 1A, assumes that the key FG nups which regulate transport are individually bi-phasic, while most theoretical and polymer physics approaches [1922] to the NPC transport problem tend to assume a homogenous structure for individual FG nups, resulting in a relatively homogenous NPC architecture. More recent advances in coarse grained simulations of the nucleoporins that consider sequence have alleviated this issue [2329] but still lack the level of detail necessary to produce potential secondary or tertiary structure. More importantly, none of the theory or simulations to date have really shed light on the specific roles of the different types of FG nups within a single NPC and the functional reason for their co-existence.…”
Section: Introductionmentioning
confidence: 99%